2018
DOI: 10.15406/ijbsbe.2018.04.00120
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric sensing of dopamine in urine samples with electrochemically activated commercially available screen-printed carbon electrodes

Abstract: Simple electrochemical pretreatment by cycling is used for the activation of commercially available screen-printed carbon electrode (Gwent Group). After the pretreatment the electrode allows for measurements of dopamine by differential pulse voltammetry in the presence of ascorbic and uric acids, and in human urine samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…A comprehensive literature review reveals that various electrochemical sensors for UA detection have been developed [11][12][13][14][15][16][17][18][19][20] including electrode modi cations with poly(procaterol) [11], N,Ndimethylformamide [12], ferrocene/Cu 2 O nanoparticles and uricase [13], mercaptobenzimidazole [14], na on membrane, ferrocene and uricase [15], sulphur-adlayer-coated gold electrode [16], and cysteamine [17]. Direct determination of UA has been reported using boron-doped diamond microelectrodes in urine samples only [18].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive literature review reveals that various electrochemical sensors for UA detection have been developed [11][12][13][14][15][16][17][18][19][20] including electrode modi cations with poly(procaterol) [11], N,Ndimethylformamide [12], ferrocene/Cu 2 O nanoparticles and uricase [13], mercaptobenzimidazole [14], na on membrane, ferrocene and uricase [15], sulphur-adlayer-coated gold electrode [16], and cysteamine [17]. Direct determination of UA has been reported using boron-doped diamond microelectrodes in urine samples only [18].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Zablocka et al [27] reported the modification of a gold electrode with a polypyrrole-mesoporous silica molecular sieves (MCM-48) nanostructured film, while Ali et al [28] presented a PANI-carbon nanotubes composite applied via a nonoxidative approach. Many electrochemical approaches with low detection limits for DA have been already presented [29,30,31,32] and most of them make use of glassy carbon, carbon paste [33], or gold electrodes, which are not disposable and whose surface is sometimes difficult to be properly cleaned or regenerated. The novelty of the realized sensor compared to those reported in literature was the use of a fast and easy-synthesizable nanocomposite film coupled with screen-printed electrodes for faster, more sensitive, disposable and cost-effective detection, which are features that could be all suitable in future POCT analysis.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Glassy carbon electrodes (GCEs) were modified with sulfonated graphene 23 or with reduced graphene oxide. 24,25 There are reports on the use of GCE modified with various composite materials: a SiO 2 -coated graphene oxide and molecularly imprinted polymers, 26 nanocomposite with carbon nanotubes, [27][28][29] NiFe 2 O 4 magnetic nanoparticles decorated with multiwall carbon nanotubes, 30 with a carbon nanohorns/poly(glycine) composite, 31 with poly(o-methoxyaniline)-gold (POMA-Au) nanocomposite, 32 with a complex of gold nanoparticles and multiwall carbon nanotubes. 33 GCE modified with a combination of fullerene (C 60 )-functionalized carbon nanotubes and ionic liquid 1-butyl-3methylimidazolium tetrafluoroborate was used to determine several catecholamine's: nor epinephrine, isoprenaline and dopamine.…”
mentioning
confidence: 99%
“…36 Modified GCEs allowed measurements of dopamine in urine at the levels of 5-30μM. [23][24][25][26][27][28][30][31][32][34][35][36][37] Polyvinylpyrrolidone/graphene modified GCE showed the detection limit of 0.5 nM dopamine. However, the recovery tests with these sensors in real samples were done at rather high concentrations, e.g.…”
mentioning
confidence: 99%